Arktinen alue Venäjän sotilaallisesta näkökulmasta - Rautala, Ari (Maanpuolustuskorkeakoulu, 2013)
Otsikon mukaisesti työ keskittyy venäläisten sotilaallisiin näkemyksiin. Arktista tutkimusta on sinällään tehty ja tehdään paljon, mutta todennäköisesti venäläistä sotilasajattelua mainitusta aiheesta ei ole tarkasteltu suomen kielellä. Työn aineisto on lähes kokonaan venäjänkielistä ja tutkittu aineisto koostuu kirjoittajista, joita – kuten Venäjällä sanotaan – pidetään alansa auktoriteetteina. Lähteet ovat julkisia. It is very likely that the Russian military presence grows in her arctic area. The evidence of this, e.g., is the plans concerning the Arctic brigades and access control to the area. Russians have no doubt that other seafarers are interested in the new sea routes due to global warming, which conse-quently means that Russians do not want to leave the new sea routes without control. This can also be justified by the fact that Russia is trying to get up the ranks of other major powers as a state whose waters cannot be sailed freely. It is of course suggested that the focus of the Russian Arctic interests is on economic issues, but ultimately the focus on the military issues cannot be ignored either. Military measures are probably not one of the first measures to be applied for resolving the Arctic disputes, but the possibility of those has to be kept in our minds.